Políticas activas de empleo juvenil en el Ecuador - Lanas Medina, Elisa (2016)
This article offers a critical analysis of the existing youth employment policies implemented by the current Ecuadorian government, with special emphasis to those included in the Substantive Law on Youth Employment, Exceptional Regulation of Working Hours, and Unemployment Insurance. The goal of this study is to contrast the government’s public policy on this matter with the approach that specialized international organisms propose to face the alarming youth unemployment rates across the world. This documents aims to generate an informed discussion over the relevance of said policies, and to explore the possibility to adjust the mechanisms proposed in the law.